Effect of ampC derepression on cefepime MIC in Enterobacterales with chromosomally encoded inducible AmpC β-lactamase. (September 2019) - Kohlmann, R.; Bähr, T.; Gatermann, S.G.
Abstract: Objectives: We aimed to evaluate the effect of ampC derepression on the cefepime MIC in different species of Enterobacterales with chromosomally encoded inducible AmpC β-lactamase. Methods: We analysed a large number of wild-type/mutant pairs ( n  = 1030 in total). Cefepime MICs were determined by broth microdilution according to EUCAST recommendations. Results: ampC derepression led to increases in MIC by up to 10 dilutions, and significant increases by > 2 MIC dilutions were common across species (744/1030 mutants (72.2%) in total). Interestingly, the frequency of cefepime S→I/S→R transitions varied considerably between species: 66.3% in Enterobacter cloacae complex (167/252 mutants), 1.1% in Klebsiella aerogenes (2/180 mutants), 18.1% in Citrobacter freundii complex (50/277 mutants), 36.4% in Hafnia alvei (59/162 mutants), 19.0% in Providencia rettgeri (4/21 mutants), 22.9% in Providencia stuartii (11/48 mutants), 12.3% in Serratia marcescens (7/57 mutants), 20.0% in Serratia liquefaciens (6/30 mutants) and 0% in Morganella morganii (0/3 mutants). Conclusions: Our data show that the cefepime MIC is often increased by ampC derepression. However, the risk of S→I/S→R transition is dependent on the species.